The efficacy of the type of instruction on second language pronunciation acquisition - Alghazo, Sharif; Jarrah, Marwan; Al Salem, Mohd Nour (Frontiers in Education, 2023)
This study investigates the efficacy of the type of instruction (i.e., perception-based vs. production-based) on second language (L2) pronunciation acquisition in an English as a foreign language (EFL) context. To achieve this objective, 60 tertiary-level Jordanian learners of English were recruited and put into two groups (30 learners in each group). Group A received 6 weeks of perception-based instruction on both segmental and suprasegmental aspects of English pronunciation, and Group B received production-based instruction over the same period and on the same aspects of pronunciation. Progress in L2 pronunciation was assessed at three time points (i.e., week 1, week 6, and week 14). Pre-, post- and delayed post-tests were run to achieve the study’s objective. A statistical analysis was conducted to analyse the data. The results show that both groups demonstrated a significant improvement in L2 pronunciation accuracy; in particular, Group A which received perception-based instruction demonstrated higher gains in segmental, syllabic, and prosodic aspects while Group B which received production-based instruction demonstrated more improvement in both global (i.e., comprehensibility) and temporal (i.e., fluency) aspects of pronunciation. However, both groups demonstrated similar gains on the delayed post-test. The findings provide implications for L2 pronunciation learners and teachers on the impact of the type of instruction on the addressed aspects of pronunciation.